Molecular perspectives in hypertrophic heart disease: An epigenetic approach from chromatin modification - Lizcano, Fernando; Bustamante, Lizeth (Frontiers in Cell and Developmental Biology, 2022)
Epigenetic changes induced by environmental factors are increasingly relevant in cardiovascular diseases. The most frequent molecular component in cardiac hypertrophy is the reactivation of fetal genes caused by various pathologies, including obesity, arterial hypertension, aortic valve stenosis, and congenital causes. Despite the multiple investigations performed to achieve information about the molecular components of this pathology, its influence on therapeutic strategies is relatively scarce. Recently, new information has been taken about the proteins that modify the expression of fetal genes reactivated in cardiac hypertrophy. These proteins modify the ADN covalently and induce changes in the structure of chromatin. The relationship between histones and DNA has a recognized control in the expression of genes conditioned by the environment and induces epigenetic variations. The epigenetic modifications that regulate pathological cardiac hypertrophy are performed through changes in genomic stability, chromatin architecture, and gene expression. Histone 3 trimethylation at lysine 4, 9, or 27 (H3-K4; -K9; -K27me3) and histone demethylation at lysine 9 and 79 (H3-K9; -K79) are mediators of reprogramming in pathologic hypertrophy. Within the chromatin architecture modifiers, histone demethylases are a group of proteins that have been shown to play an essential role in cardiac cell differentiation and may also be components in the development of cardiac hypertrophy. In the present work, we review the current knowledge about the influence of epigenetic modifications in the expression of genes involved in cardiac hypertrophy and its possible therapeutic approach